Evaluation of wood volume in young eucalyptus trees with and without irrigation - Adriano da S. Lopes; Marcos V. Folegatti; Gabriel Q. de Oliveira; Eder D. Fanaya Júnior; Isabela B. Belchior; Kelvin R. M. Brito (Revista Brasileira de Engenharia Agrícola e Ambiental)
Irrigation management has mostly been performed without criteria and, studies in relation to field-irrigated eucalyptus development are scarce. The aim of this study was to evaluate wood volume equations based on stem (trunk) diameter of two eucalyptus hybrids in initial development, with and without irrigation. The experiment was set up in Aquidauana, State of Mato Grosso do Sul, Brazil, from April, 2011 to March, 2012, with the eucalyptus hybrids, Eucalyptus grandis x Eucalyptus camaldulensis (Grancam) and Eucalyptus urophylla x Eucalyptus grandis (Urograndis). Evaluations were performed during the first year of crop development in which five mathematical models were tested for estimation of wood volume (Berkhout; Koperzik & Gehrhardt; Exponential; Brenac; Hohenald & Krenn). The best models for estimation of wood volume of young plants are Brenac, Exponential and Hohenald & Krenn. The Brenac equation shows highest precision for estimating wood volume as a function of diameter at 5 cm height from the ground, with precision greater than 99% for plants up to 12 months of age, regardless of the use of irrigation.